El desplazamiento de los espacios cívicos. La mediación divina entre Ptolis y Mantinea - Tsiolis, Vasilis (ARYS. Antigüedad: Religiones y Sociedades, 2020)
This paper aims to connect the legend of the heroine Antinoe, related by Pausanias in the context of a refoundation of Mantinea, with the socioeconomic an religious dynamics of the new location area, previous to the city foundation as an urban centre. The legend, which seems to be an attempt to explain the toponym Ptolis gave to the hill nearby the city, as well as to justify etymologically the city name Mantinea, is here analysed in combination with topographical data, epigraphic evidence and some mantinean cults. As a result, an hypothesis is formulated concerning Antinoe and the nature of the cults implicated in the urbanization process of the district.